Analysis of Tree Ordinances in Cuyahoga County, Ohio, and Recommendations for a Countywide Policy to Protect Trees - Jenish Venancius; Robert Brand; Andrew Morris; Karen Mulloy (Ohio Journal of Public Health, 2024)
Background: Trees and urban forests have significant public health benefits as well as providing both climate mitigation and adaptation impacts. The tree canopy in Cuyahoga County, Ohio, had suffered a 6% decline between 2010 and 2017, and some cities in the county had suffered as much as an 11% decrease by 2023. Methods: All current county tree ordinances were analyzed. A review and analysis of the relevant scientific literature and similar ordinances of other cities and counties were completed. The most suitable sections of the tree ordinances were determined by selecting components that had the strongest attributes and compiling these to make a single, robust model ordinance. Results: The results of this study recommended that an ideal tree ordinance must address or mention permitting for the removal of otherwise healthy trees, while allowing for the lawful removal of trees that are diseased or pose a threat to persons or property. Balancing the interests of private landowners with that of the general public health interests would be key to the success and implementation of such an ordinance. Conclusion: The study found that by compiling different sections of various existing tree ordinances and providing suggestions for improvements, a model city ordinance was both feasible and scalable. This model tree ordi-nance would then be used by future lawmakers of Cuyahoga County, Ohio, or its constituent municipalities in order to effectively protect tree canopy.
Keywords: Tree canopy; Climate change; Public health benefits; Model tree ordinance